Effect of Phosphorus, Iron, Zinc, and Their Combined Deficiencies on Photosynthetic Characteristics of Rice (Oryza sativa L.) Seedlings - Dapeng Gao; Cheng Ran; Kun Dang; Xiaolei Wang; Yunhe Zhang; Yanqiu Geng; Shuying Liu; Zhengwen Guan; Liying Guo; Xiwen Shao (Agronomy, 2023)
Combined elemental deficiencies are more complex and insidious physiological metabolic responses than single elemental stresses. To determine the effects of phosphorus (P), iron (Fe), zinc (Zn), and their deficient combinations on photosynthetic characteristics of rice seedlings, we investigated their effects on dry weight, chlorophyll (Chl) content, rapid photosynthetic carbon assimilation CO2 responses, and Chl fluorescence in four-week-old rice (CB9 and BJ1 cultivars) seedlings. The results showed that the dry matter, maximum carboxylation efficiency (Vc,max), and maximum electron transfer efficiency (Jmax) of seedlings were all reduced to different degrees under the element deficiency treatments. JIP-test analysis showed that the decrease in the concentration of active PSII reaction centers (RC/ABS) under -Zn treatment was the main reason for the inhibition of performance index PIABS. The -P treatment reduced RC/ABS and inhibited electron transfer (ψEo). Primary photochemical reactions (φPo) of -P-Zn treated seedlings were also inhibited compared to the -P treatment. The -Fe and -Fe-Zn treatments inhibited photosynthesis most severely, which not only reduced RC/ABS but also severely inhibited φPo and ψEo. Notably, the -P-Fe and -P-Fe-Zn treatments of the CB9 improved the RC/ABS, alleviating the limitation of Fe deficiency. These results help enhance the understanding of the complex relationship between nutrient balance and photosynthesis, especially for P, Fe, Zn, and their combined deficiency.